Effects of Melittin on the Production of Matrix Metalloproteinase-1 and -3 in Rheumatoid Arthritic Fibroblast-Like Synoviocytes - Seong-Su Nah; Eunyoung Ha; Se Hwan Mun; Hye-Jin Won; Joo-Ho Chung (Elsevier, 2008)
Bee venom (BV) has been used in patients with rheumatoid arthritis, a condition characterized by rheumatoid joint destruction mediated, in large part, by matrix metalloproteinases (MMPs). We investigated the effects of melittin, a major component of bee venom, on the production of MMPs in human rheumatoid arthritic fibroblast-like synoviocytes (FLS). Lipopolysaccharide (LPS)-stimulated MMP3 production was significantly inhibited by melittin, which also inhibited LPS-induced DNA binding by nuclear factor κ B (NF-κ B). Mellitin had no effect on IL-1β -or TNF-α -induced MMP1 or MMP3 production and did not decrease LPS-induced secretion of MMP1. Taken together, these findings suggest that melittin may exert its anti-rheumatoid effects, at least in part, by inhibiting MMP3 production, most likely through inhibition of NF-κ B activity. Keywords:: rheumatoid arthritis, melittin, matrix metalloproteinase-1 and -3